Effect of annealing on microstructure evolution and mechanical property of cold forged magnesium pipes - Lu, Liwei (2013)
Microstructure evolution of pure Mg pipes forged at room temperature during annealing is investigated by electron backscatter diffraction with special focus on the textures and static recrystallization (SRX) mechanism. It is found that a series of twins, {1012}(1011), {1012} - {1012}, {1013}(3032), {1012} - {0112}, {1013} - {1012}, and {1011}(1012), turn up in the as-forged Mg pipes, which play a crucial role in the SRX through acting as recrystallization sites and in refining grains during annealing, especially the contraction twins and triple junctions. Using several analytic techniques, the SRX textures and grain boundaries are characterized during the SRX formation and growth, and the restoration mechanism is discussed based on the impact of annealing temperature and time. Moreover, the annealing conditions are found to be key to affecting micro-hardness of Mg pipes by tailoring recrystallization, grain growth, and recovery and recrystallization duration.